2016
DOI: 10.1245/s10434-016-5707-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Predictors of Resection and Survival in Locally Advanced Stage III Pancreatic Cancer: Does the Nature of Chemotherapy Regimen Influence Outcomes?

Abstract: In LAPC, use of FOLFIRNOX and/or gemcitabine/nab-paclitaxel is associated with improved survival compared with older chemotherapy regimens, regardless of eventual resection. Tumor location and relationship to certain vasculature are important determinants of resection in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Preoperative serum CA 19‐9 level was a prognostic factor for DFS. Bednar et al reported that radiation, ≧2 lines of chemotherapy, and surgery were significant independent prognostic factors for OS in 92 patients with initial UR‐LA (20% resectability). However, CA19‐9 level was not included in the multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative serum CA 19‐9 level was a prognostic factor for DFS. Bednar et al reported that radiation, ≧2 lines of chemotherapy, and surgery were significant independent prognostic factors for OS in 92 patients with initial UR‐LA (20% resectability). However, CA19‐9 level was not included in the multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic therapy for advanced pancreatic adenocarcinoma (including metastatic disease) has improved with the availability of more effective chemotherapeutic regimens such as FOLFIRINOX (median OS 11.1 months, RR 31.6%) and gemcitabine with nab-paclitaxel (median OS 8.5 months, RR 23%). [ 9 , 10 ] Advances in the chemotherapeutic treatment of metastatic pancreatic adenocarcinoma have been extrapolated to other potentially resectable categories of pancreatic adenocarcinoma [ 9 15 ]. More aggressive multimodality treatments have been employed for the management of resectable and borderline resectable tumors in addition to locally advanced tumors [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…24 FFX and GEM plus nab-paclitaxel are now considered standard first line treatment options in metastatic pancreatic cancer. 2,25,26 However, FFX has been reported to have a stronger adverse effect than nab-paclitaxel. 24 In the present study, tumors shrunk by 80% upon administration of FFX twice.…”
Section: Discussionmentioning
confidence: 99%